Experiential-based training to improve literacy skills of traditional game for tourism workers - Entoh Tohani; Sugito Sugito (Jurnal Pendidikan Vokasi, 2020)
This research aims to develop the literacy skills on the traditional game for tourism village workers through experiential-based training. Traditional game literacy is attitudes, knowledge, and skills in managing traditional games to make it more meaningful for life, sustainable, and keep people away from negative social changes. This research is participatory action research and conducted on 25 workers located in the Yogyakarta batik tourism village. Data collected and analyzed by using qualitative methods. The research results showed that the action of skill development able to the target group realized the importance of traditional game literacy in the context of developing tourism services, having the ability to manage tourism services based on traditional games, and forming traditional game tourism management. Therefore, this skill development needs to be carried out continuously and meaningfully by optimizing the involvement of all parties involved in tourism development.